The place of steroid-antibiotics and early bougienage combination in the treatment of caustic esophageal burns in childhood - Tanyel, F. Cahit; Büyükpamukçu, Nebil; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 1988)
The results of treatment using steroids, antibiotics and early bougienage combination in 31 patients with mucosal penetrating caustic esophageal burns were evaluated retrospectively. In 10 patients, who ingested caustics other than strong alkalies and acids, there were no strictures and no complications. In 12 acid ingestion cases, there were no complications, but three strictures. In nine patients, who ingested caustic soda, there were two perforations, one of which resulted in death. There were strictures in seven of the remaining eight patients. Therefore, the combined use of steroids, antibiotics and early bougienage is suggested to be of limited value after strong alkali ingestion.
Keywords: corrosive ingestion; caustic esophagitis; bougienage; esophageal stricture